2020
DOI: 10.1002/ddr.21649
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin ameliorates carbon tetrachloride‐induced liver fibrosis in mice through inhibition of the NLRP3 inflammasome

Abstract: Liver fibrosis is characterized by the activation of hepatic stellate cells (HSCs) and accumulation of the extracellular matrix. There are limitations in the current therapies for liver fibrosis. Recently, oridonin was shown to induce apoptosis in HSCs. Thus, we aimed to determine the roles of oridonin in chronic liver injury and fibrosis. Liver fibrosis was induced by CCl 4 in mice injected intraperitoneally with oridonin for 6 weeks. The administration of oridonin significantly attenuated liver injury and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…A same story occurs in CCl 4 toxicity. The CCl 4 is able to induce liver fibrosis via inflammation, oxidative stress and stimulates apoptosis ( Liu et al, 2020a ; Munakarmi et al, 2020 ; Zhang et al, 2020b ). In inhibition of CCl 4 -mediated liver injury, curcumin down-regulates TGF-β1/Smad3 signaling pathway ( Peng et al, 2018 ).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…A same story occurs in CCl 4 toxicity. The CCl 4 is able to induce liver fibrosis via inflammation, oxidative stress and stimulates apoptosis ( Liu et al, 2020a ; Munakarmi et al, 2020 ; Zhang et al, 2020b ). In inhibition of CCl 4 -mediated liver injury, curcumin down-regulates TGF-β1/Smad3 signaling pathway ( Peng et al, 2018 ).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…reported that oridonin can target NLRP3 to exert its antiinflammatory activity and that the dose needed for inhibition NLRP3 was about 10 times lower than the dose needed for TNF-α inhibition (He et al, 2018). In addition, the inhibition of oridonin on NLRP3 was confirmed in LPS-induced acute lung injury (Yang et al, 2019) and carbon tetrachloride-induced liver fibrosis (Liu, Qin, et al, 2020) in mice.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, this compound could inhibit angiogenesis and EMT related to VEGF-A ( Li C. Y. et al, 2018 ), block Notch signaling pathway to inhibit the growth and metastasis of breast cancer ( Xia et al, 2017 ), and induce autophagy to promote apoptosis ( Li and Yang, 2015 ). In addition to its above anti-tumor effects, there is growing evidences that oridonin exhibits other anti-tumor activities such as colorectal cancer ( Bu H. et al, 2019 ), pancreatic cancer ( Liu D. et al, 2020 ), gallbladder cancer ( Chen, et al, 2019 ), prostate cancer ( Lu et al, 2017 ) and so on. Given that pathway defects have been recognized by most chemotherapies, oridonin may be a logical botanical for future researches of tumor adjuvant therapy.…”
Section: Pharmacologymentioning
confidence: 99%